Wired/wireless internet communications : 15th IFIP WG 6.2 International Conference, WWIC 2017, St. Petersburg, Russia, June 21-23, 2017, Proceedings /: 15th IFIP WG 6.2 International Conference, WWIC 2017, St. Petersburg, Russia, June 21-23, 2017, Proceedings. (2017) - Unknown
No abstract available